2010
DOI: 10.1111/j.1749-7345.2009.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Density of Vibrios in Hemolymph and Hepatopancreas of Diseased Pacific White Shrimp, Litopenaeus vannamei, from Northwestern Mexico

Abstract: Vibriosis is one of the most widespread infectious diseases of cultured shrimp in Mexico; as a result, the Research Centre for Food and Development (CIAD, for the Spanish wording) offers a diagnostic service to the shrimp farmers where they bring samples of diseased shrimp as judged by themselves. Hemolymph (HL) and hepatopancreas (HP) of diseased Litopenaeus vannamei were analyzed from five regions of Northwestern Mexico (from 2001 to 2006) in tiosulphate citrate bile sacharose (TCBS) agar; a total of 5912 sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 20 publications
0
17
0
8
Order By: Relevance
“…Mexican shrimp production depends mainly on the northwestern states, and Sonora, Sinaloa, Nayarit, and Baja California reported a joint production in 2011 of 105,218 tons, which was worth 4.263 billion Mexican pesos (40) (http://www.conapesca.sagarpa.gob.mx/wb/cona/anuario_2011). Unfortunately, the rapid growth of this industry has increased the number of epizootics associated with infectious diseases in Mexico and other countries in Latin America, and significant losses of shrimp production have occurred because of disease caused by viruses, such as infectious hypodermal and hematopoietic necrosis virus (IHHNV), Taura syndrome virus (TSV), and white spot syndrome virus (WSSV) (1), and bacteria, such as the necrotizing hepatopancreatitis bacterium (NHP-B) (2,3) and Vibrio (4). Vibriosis is a disease caused by bacteria belonging to the Vibrio genus that produce necrotic lesions in the tissues of infected organisms (5,6).…”
mentioning
confidence: 99%
“…Mexican shrimp production depends mainly on the northwestern states, and Sonora, Sinaloa, Nayarit, and Baja California reported a joint production in 2011 of 105,218 tons, which was worth 4.263 billion Mexican pesos (40) (http://www.conapesca.sagarpa.gob.mx/wb/cona/anuario_2011). Unfortunately, the rapid growth of this industry has increased the number of epizootics associated with infectious diseases in Mexico and other countries in Latin America, and significant losses of shrimp production have occurred because of disease caused by viruses, such as infectious hypodermal and hematopoietic necrosis virus (IHHNV), Taura syndrome virus (TSV), and white spot syndrome virus (WSSV) (1), and bacteria, such as the necrotizing hepatopancreatitis bacterium (NHP-B) (2,3) and Vibrio (4). Vibriosis is a disease caused by bacteria belonging to the Vibrio genus that produce necrotic lesions in the tissues of infected organisms (5,6).…”
mentioning
confidence: 99%
“…Whilst WSSV was sometimes detected during outbreaks of BRS, vibriosis was always present with the CAIM 1792 strain predominating in the haemolymph of all shrimp sampled. The density of vibrio in haemolymph and the hepatopancreas was similar to Litopenaeus vananmei shrimp with vibriosis cultured in northwestern Mexico (Soto-Rodriguez et al 2010).…”
Section: Discussionmentioning
confidence: 81%
“…The minimum inhibitory concentration (MIC) was determined for 29 bacterial isolates in Müller-Hinton broth containing 2.5% NaCl using a microdilution method (Rangdale et al 1997, Soto-Rodriguez et al 2010. Dominant yellow colonies picked from the TCBS plates were used to prepare a bacterial suspension to determine the MIC of oxytetracycline (OTC), enrofloxacine (ENR), florfenicol (FLO), and norfloxacine (NOR).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between weight and microbiota of Vibrio in shrimp hepatopancreas has been reported by Soto Rodríguez et al (9). In Shrimp Diseases, the authors cited found that vibrio density in hepatopancreas individuals weighing 8-12 g had a greater bacterial loads than individuals weighing 0.26-4.0 g.…”
Section: Discussionmentioning
confidence: 84%